Demography and innovative entrepreneurship - Werner Bönte; Oliver Falck; Stephan Heblich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Demographic change will be one of the major challenges for economic policy in the developed world in the next decades. In this article, we analyze the relationship between age structure and the number of startups. We argue that an individuals decision to start a business is determined by his or her age and, therefore, that a change in a regions age distribution affects the expected number of startups in the region. Using German regional data, we estimate a count-data model and find that the expected number of startups is positively influenced by the fraction of individuals of working age2064 years old. A more detailed analysis of the working-age distribution suggests that startups in knowledge-based (high-tech) manufacturing industries are affected by changes in this distribution whereas firms in other industries are not. In particular, increases in the fraction of individuals in the 2030 age range and individuals in the 4050 age range have a positive effect on the number of high-tech startups.
Keywords: J1; L26; O3; R11; 330; Demography; Age Distribution; Entrepreneurship; Innovation; Region; Unternehmensgründung; Lebensalter; Unternehmer; Hochtechnologiesektor; Regionale Bevölkerungsentwicklung; Altersstruktur der Bevölkerung; Deutschland